Examining It-Based Human Resources Strategies in Islamic Higher Education and Islamic Boarding Schools In Indonesia - Musyaffa, A A; Muktamar B, Ahmad; Ichsan, Ichsan; Yuli Setianto, Akbar; Hasanah, Mila (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This study examines IT-based HR development strategies in Islamic higher education and boarding schools in Indonesia, focusing on the Faculty of Tarbiyah at Universitas Islam Negeri Sultan Thaha Saifuddin, Jambi. It also explores the integration of IT in primary school teacher of education training programs. The research employed interviews, surveys, and document analysis using a case study approach. Participants included faculty members, administrators, students, and teachers/administrators from selected Islamic boarding schools. The findings show the faculty's progressive integration of IT-based HR development strategies. These include Learning Management Systems (LMS), online training modules, virtual classrooms, and educational apps. These tools improve instruction, student engagement, and administrative efficiency. The study also highlights the inclusion of IT in basic school teacher education training programs. Incorporating IT skills into the curriculum is crucial for prospective teachers to effectively use educational technologies in their classrooms. This research enhances the understanding of IT-based HR development strategies in Indonesia's Islamic higher education and boarding schools. It guides educational institutions and policymakers for better integration of IT in teacher education programs, promoting effective HR development strategies, and improving overall educational quality.